This woman is called Jasna : A sketch for a historical novel in cinematic form (Pangoil Publishers, 2022)
The work 'This woman is called Jasna' started in 2013 as a one-off performance with no intention of becoming a five year collaborative project that resulted in a series of exhibitions and public events, ten spoken word audio-visual performances, four experimental films, an array of texts and visual materials, and two artist books.
English
Keywords: TR845-899 Technology- Cinematography